Problems of healing chronic wounds - N. M. Babenko; O. B. Litvinova; S. B. Pavlov; M. V. Kumechko; V. V. Komarchuk (Сучасні медичні технології)
Aim. The work aimed to analyze and highlight the problems of chronic wound healing and modern methods of stimulation of reparative processes according to literature sources.